Pemberdayaan Ekonomi Para Difabel Sebagai Pramusaji Di Difable Cafe Sondakan Laweyan Surakarta - Avany Aisya Alfiani Alfiani; Yuhastina; Danang Purwanto (Jurnal Pemberdayaan Masyarakat, 2022)
Difable is one part of Indonesian citizens in their daily activities. One of the problems experienced by people with disabilities is getting negative stigma, discrimination, and the limited availability of job opportunities. The research method uses a qualitative descriptive approach. The research location is at Difable cafe Jl. Madubronto No. 08, Sondakan Purwosari, Laweyan, Surakarta, Central Java. Collecting data sources through interviews, observation, and documentation. The sampling technique used was purposive sampling technique, namely to 8 informants. The data validity test technique uses triangulation of data sourced from Difable Cafe customers. Meanwhile, the data analysis technique used the theory of Miles and Huberman, namely data reduction, data presentation, and drawing conclusions. The results of the empowerment show that the Difable Cafe carries out an empowerment process that is said to be able to increase the empowerment of people with disabilities and be able to empower the economy of people with disabilities. The empowerment of waiters is also quite successful which is carried out by Difable Cafe for people with disabilities. This empowerment aims to improve quality, improve the economy for daily needs, and reduce the number of unemployed persons with disabilities in Indonesia.